Controlled semantic processes within and between the two cerebral hemispheres. Issue 1 (2nd January 2017) - Peleg, Orna; Eviatar, Zohar
ABSTRACT: To test the separate and combined abilities of the two cerebral hemispheres to perform controlled semantic selection and integration processes, Hebrew readers saw pairs of words and had to decide whether the two words were semantically related. The first word in each pair was presented centrally. The second word was presented in the left, right, or central visual field (LVF, RVF, and CVF). We compared response latencies for related pairs in two conditions: In the ambiguous condition, the first word was a homograph (either homophonic or heterophonic) and the second word was related to either its dominant or subordinate meaning. In the unambiguous condition, homographs were replaced with unambiguous control words. Irrespective of VF or homograph type, response times for ambiguous pairs were significantly longer than for unambiguous pairs only when targets were related to the subordinate meaning of the homograph. In the left hemisphere (RVF/LH), this ambiguity effect was larger for heterophones than for homophones, whereas in the right hemisphere (LVF/RH), similar patterns were observed for both types of homographs. Finally, performance patterns in the CVF revealed the same patterns as those in the RVF/LH, and were different from those in the LVF/RH. The implications of these results are discussed.